Peningkatan kepatuhan pajak melalui peningkatan kualitas pelayanan pajak kepada wajib pajak - Aa’zza, Azka Al (Maliki Interdisciplinary Journal, 2024)
Taxpayer compliance is awareness in fulfilling tax obligations which is reflected in the condition of taxpayers understanding and trying to understand all provisions of tax laws and regulations, filling out tax forms completely and clearly, calculating the amount of tax owed correctly, and paying taxes on their obligations on time.